The Doors - Stone, Oliver; Jahnson, Randall; Kilmer, Val, 1959-2025; Ryan, Meg; Dillon, Kevin; Doors (Musical group); Carolco Pictures Inc.; Universal Studios Home Video (Firm) (Universal City, CA : Universal Studios Home Video, 1999)
Dramatized biography of Jim Morrison and the musical group which typified the 1960's.
Originally released as a motion picture in 1991.
Features: audio commentary, long form videos, Dance on fire, The Doors live at the Hollywood Bowl, and The soft parade, new LA woman video, new print of Unknown soldier, Ray Manzarek's student films, excerpts from John Densmore's play, Robby Krieger performing a new version of The end, outtakes from The Door's archives, over 100 rare collectibles plus Doors' personal artifacts.
Director of photography, Robert Richardson; production designer, Barbara Ling; editor, David Brenner; music, The Doors.
Val Kilmer, Meg Ryan, Kevin Dillon, Kyle MacLachlan, Frank Whaley, Billy Idol, Michael Madsen, Kathleen Quinlan.
MPAA rating: R.
DVD Dolby stereo.
Keywords: Morrison, Jim, -- 1943-1971 -- Drama; Doors (Musical group) -- Drama; Video recordings for hard of hearing people; Feature films; Biographical films